A Software and Hardware IPTV Architecture for Scalable DVB Distribution. (14th December 2009) - Acher, Georg; Fliegl, Detlef; Fuhrmann, Thomas
Abstract : Many standards and even more proprietary technologies deal with IP-based television (IPTV). But none of them can transparently map popular public broadcast services such as DVB or ATSC to IPTV with acceptable effort. In this paper we explain why we believe that such a mapping using a light weight framework is an important step towards all-IP multimedia. We then present the NetCeiver architecture: it is based on well-known standards such as IPv6, and it allows zero configuration. The use of multicast streaming makes NetCeiver highly scalable. We also describe a low cost FPGA implementation of the proposed NetCeiver architecture, which can concurrently stream services from up to six full transponders.